Suicide attempts and eating disorders in adolescents, the mental health wave of the second year of the COVID-19 pandemic: A paediatric emergency department perspective - Cozzi, Giorgio; Grillone, Alberto; Zuliani, Elettra; Giangreco, Manuela; Zanchi, Chiara; Abbracciavento, Giuseppe; Barbi, Egidio; Amaddeo, Alessandro (Frontiers in Pediatrics, 2023)
Aim: We compared adolescents’ visits to a tertiary-level paediatric emergency department (PED) in Italy during the pre-pandemic year and the first and second years of the COVID-19 pandemic, focusing on mental health presentations. Methods: This was a retrospective study. We collected the number of visits, the demographical features, triage codes, discharge diagnoses, and outcomes of adolescents 13-17 years old who accessed the PED from 1 March 2019 to 28 February 2022. Results: During the study period, 13410 adolescents accessed the PED. The number of visits related to mental health problems was 304 (6.4%) in the second year of the pandemic and 306 (5.6%) in the pre-pandemic year, p = 0.07. In the same periods, females’ prevalence was higher, 220 (72.4%) vs 197 (64.4%), p = 0.03. The absolute number of subjects needing admission increased, 44 vs 34, p = 0.21, and more urgent psychiatric consultations were needed, 161 vs 114, p <0.0001. The number of suicide attempts was 23 vs 8, +188%, p = 0.01. The number of adolescents with eating disorders was 21 vs 5, +320%, p = 0.001. Conclusion: PED visits for suicide attempts and eating disorders in adolescents sharply increased in the second year of the pandemic.